Hemodynamically significant anemia as an indication of transfusion in preterm infants - Marwa Mohamed Farag; Mohamed Alaa Eldin Hassan Thabet; Ahmed Adel Hassan El Beheiry; Bahaa Salah-El Din Hammad; Mohammed Attia Khalifa; Amany Abdel Hamed Elsebaee (Italian Journal of Pediatrics)
Abstract Background To transfuse or not to transfuse premature infants” is still one of debatable issues in neonatal care that has not been completely solved. Recognizing hemodynamically significant (HS) anemia might be part of the solution. Our purposes were to investigate the hemodynamic effects of late onset anemia and red blood cells (RBCs) transfusion on premature neonates with gestational age 28–32 weeks and to tailor transfusion needs based on hemodynamic variables and Hb/HCT level. Methods In the current study, 36 anemic preterm infants with a gestational age of 28–32 weeks and a postnatal age of 3–9 weeks, all having a hematocrit (HCT) level below 30% and being candidates for red blood cell (RBC) transfusions, were compared to 36 non-anemic infants with HCT levels of 30% or higher in terms of hemodynamic parameters during their initial scans. Each anemic infant underwent a second scan 24 h after receiving RBC transfusions. The hemodynamic parameters assessed included left ventricular cardiac output (LVO) and the flow velocities in the renal (RA), anterior cerebral (ACA), and celiac (CA) arteries, measured using functional echocardiography and Doppler imaging. The hemodynamic changes were related to the presence of clinical signs in the anemic infants. Results LVO, stroke volume (SV), heart rate (HR), and ACA-peak systolic velocity (PSV) were significantly increased in anemia of prematurity and significantly decreased after RBCs transfusions. With an area under the ROC curve of 0.862, LVO displayed the highest diagnostic performance for HS-anemia of prematurity. Conclusions LVO, SV, HR, ACA-PSV, hemodynamic parameters can be used for diagnosing HS-anemia and can provide objective criteria for identifying patients in need of RBCs-transfusions. They also help in monitoring response of RBCs-transfusion in anemic preterm infants. Those cut off measures require validation by future studies.